Trimetazidine Attenuates Heart Failure by Improving Myocardial Metabolism via AMPK - Shu, Hongyang; Hang, Weijian; Peng, Yizhong; Nie, Jiali; Wu, Lujin; Zhang, Wenjun; Wang, Dao Wen; Zhou, Ning (Frontiers in Pharmacology, 2021)
Energic deficiency of cardiomyocytes is a dominant cause of heart failure. An antianginal agent, trimetazidine improves the myocardial energetic supply. We presumed that trimetazidine protects the cardiomyocytes from the pressure overload-induced heart failure through improving the myocardial metabolism. C57BL/6 mice were subjected to transverse aortic constriction (TAC). After 4 weeks of TAC, heart failure was observed in mice manifested by an increased left ventricular (LV) chamber dimension, an impaired LV ejection fraction evaluated by echocardiography analysis, which were significantly restrained by the treatment of trimetazidine. Trimetazidine restored the mitochondrial morphology and function tested by cardiac transmission electron microscope and mitochondrial dynamic proteins analysis. Positron emission tomography showed that trimetazidine significantly elevated the glucose uptake in TAC mouse heart. Trimetazidine restrained the impairments of the insulin signaling in TAC mice and promoted the translocation of glucose transporter type IV (GLUT4) from the storage vesicle to membrane. However, these cardioprotective effects of trimetazidine in TAC mice were notably abolished by compound C (C.C), a specific AMPK inhibitor. The enlargement of neonatal rat cardiomyocyte induced by mechanical stretch, together with the increased expression of hypertrophy-associated proteins, mitochondria deformation and dysfunction were significantly ameliorated by trimetazidine. Trimetazidine enhanced the isolated cardiomyocyte glucose uptake in vitro. These benefits brought by trimetazidine were also removed with the presence of C.C. In conclusion, trimetazidine attenuated pressure overload-induced heart failure through improving myocardial mitochondrial function and glucose uptake via AMPK.